MOLECULAR BIOMARKER-BASED PERSONALIZED THERAPY ALGORITHM IN ENDOCRINE INFERTILITY - Anvarova, SH.A.; Shukurov, F.I.; Tulametova , SH.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Endocrine infertility (EI) is one of the leading reproductive disorders among women of reproductive age. This study explored diagnostic approaches using molecular and metabolic biomarkers and developed individualized treatment algorithms in the context of key pathophysiological factors such as polycystic ovary syndrome (PCOS), hypothyroidism, and hyperprolactinemia. Ninety women aged 18–40 years participated in the study, and their hormonal profiles (AMH, FSH, LH, PRL, TSH, FT4, Leptin, INHB), ultrasound parameters (AFC and endometrial thickness), and molecular indicators (Leptin/Adiponectin ratio and INHB/AMH index) were analyzed. ROC analysis and logistic regression results showed that the model combining AMH, Leptin, and AFC achieved a diagnostic accuracy of AUC=0.91, while the INHB/AMH index predicted ovulatory response with AUC=0.88. These findings laid the foundation for the development of a personalized therapy algorithm based on molecular biomarkers, enabling optimized individualized treatment strategies and improved reproductive outcomes in patients with endocrine infertility.